Law and order in Sung China - McKnight, Brian E. (Cambridge studies in Chinese history, literature and institutions, 1992)
In examining these aspects of Chinese law enforcement, the study describes the change in balance from a predominantly military force to a civil bureaucracy, with accompanying problems the state faced in finding a sufficient number of qualified and trustworthy law-enforcement agents. McKnight analyzes the procedures and policies that governed law-enforcement practices, from policing and apprehension to the judicial process of convicting criminals, and finally to methods of punishment